Can self-esteem mediate social support and self-adjustment in adolescents? - Witadi, Jihan Tamara Khairunnisa; Rusdiana, Fendi Krisna (University of Merdeka Malang, 2025)
The background of this study is based on the importance of social support and self-esteem in the adaptation process of adolescents, especially in the context of life in pesantren. This study aimed to examine the effect of social support on adolescent self-adjustment with self-esteem as a mediating variable. The participants of this study were 120 santris who completed three psychological scales: social support, self-esteem, and self-adjustment. Data were analyzed using path analysis with JASP software version 0.19.3. The results showed that social support significantly influenced self-adjustment both directly (β = 0.399; p < 0.001) and indirectly through self-esteem as a partial mediator (β = 0.171; p < 0.001), with a total effect of β = 0.570 (p < 0.001). These findings highlight the important role of social support in promoting adolescents' adjustment, both directly and through improving self-esteem, and suggest the importance of strengthening the social support system in the home education environment.